If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3=1/3(10x+3)
We simplify the equation to the form, which is simple to understand
3=1/3(10x+3)
Simplifying:
3=0.333333333333*(10x+3)
Reorder the terms in parentheses
3=+(+3.33333333333x+1)
Remove unnecessary parentheses
+3=+3.33333333333x+1
We move all terms containing x to the left and all other terms to the right.
-3.33333333333x=+1-3
We simplify left and right side of the equation.
-3.33333333333x=-2
We divide both sides of the equation by -03.33333333333 to get x.
x=0.600000000001
| 13=.8(x+20) | | 1=2.5(5x+8) | | (48-2x)(62-2x)=0 | | v^-3/v^-6 | | -8x-6=-2x-60 | | -n=1/3^-5 | | (x^2-4x-2)x(x+7)= | | 3(2p+3q)+-4q= | | -7x-6=-12x-41 | | -n=1/4^-4 | | (x^2-4x-2)(x+7)= | | -n=1/9^-2 | | -14x+6=-6x+38 | | -14x+6=-6+38 | | 3x-2=-4x+33 | | 17x-2=8x+88 | | -n=1/5^-5 | | 9y-1=-10+12y | | -5(7n-4)+3= | | 2y-14=4y+4 | | P=2(26)+2(91) | | 5y+6y-81=7y+102+65 | | 3t^4=8t | | x+x+125000=550000000 | | 12x+8y-12=0 | | 4*x-9/2+12=0 | | 51x^2-5x-4= | | x+x+4=238 | | -(6y+5)-(-5y-7)=-5 | | 14-2x+39x-18x=256-60x-657x | | 13-42/7 | | 7+3p-4=9p+10-5p |